Challenges of Frontline health workers on reduction of anaemia among adolescents: A Qualitative enquiry - Yadav, Priyanka; Kumar, Alok; Kansal , Sangeeta (Indian Journal of Community Health, 2024)
Purpose: High prevalence of anaemia is a severe public health problem in several low- and middle-income countries like India. In adolescents, anaemia has been linked to impaired physical and mental development and increases reproductive morbidities among adolescent girls during their womanhood. To tackle this high prevalence, number of government programs have been launched in India. However, a slow decline in the prevalence of anaemia has been reported in Indian adolescents over the recent past. Therefore, it is important to unfold the issues in reduction of prevalence of anaemia and the current study was carried out to identify challenges in reducing anaemia among adolescent girls. Methods: 33 frontline health workers were recruited from 6 randomly selected villages (out of 6, 2 villages were having population less than 2000, 2 villages were having population 2000 to 5000 and 2 villages were having more than 5000 population) of Kashi Vidyapeeth block, Varanasi. between January 2022 to April 2022. In-depth, face-to-face interviews were carried out in local language using an interview guide. All the interviews were recorded and transcribed verbatim. Transcribed data was analysed manually for theme extraction. This study was granted ethical permission by the Institutional Ethics Committee. Results: Following major themes were extracted during the data analysis: (i) Poor knowledge about adolescent health-related issues; (ii) non-adherence to program guidelines; (iii) Irregularity in the supply chain; (iv) Beneficiary’s lack of interest in only education about anaemia in the community; (v) Excessive administrative burden; (vi) Dissatisfaction in terms of monetary remuneration. Conclusions: The emerging findings throw light on the knowledge & perspective of Frontline health workers about program guidelines and also highlights the different challenges in implementing anaemia prevention strategies faced by them at the grass root level.